Presence of an accessory spleen in the gastrosplenic ligament: Its histological observation and clinical consequences - Jyothsna Patil; Naveen Kumar; Satheesha B Nayak; S Swamy Ravindra; Anitha Guru; Ashwini P Aithal; Melanie R D'Souza (Wolters Kluwer Medknow Publications, 2015)
Accessory or supernumerary spleens are congenital in occurrence. Its presence may result in differential diagnosis or exhibit continued symptoms after therapeutic splenectomy. We report here a case of accessory spleen (AS), which was remarkably larger in size was found within the gastro-splenic ligament, adherent to its anterior layer. It received an independent vascular supply from splenic vessels supplying the main spleen (MS). Its histological architecture was in close resemblance to that of MS, but with the deficiency of white pulp. Failure to remove AS during main splenectomy done for pathological conditions may result in failure of resolving the condition due to which the pathological condition persists. Occurrence of ASs may also be confused for enlarged lymph nodes or neoplastic growth in the tail of pancreas, gastrointestinal tract and adrenal glands.